2016
DOI: 10.1111/1477-8947.12088
|View full text |Cite
|
Sign up to set email alerts
|

Key factors that influence households’ tree planting behaviour

Abstract: Despite a decrease in indigenous forests and a growing demand for tree products in developing countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
(119 reference statements)
3
7
0
Order By: Relevance
“…The results concede with other findings in that households tend to minimize labor inputs, leading to low quantities and qualities of tree farm outputs [53]. As observed by similar studies from the tropics, farmers with more land resources are able to carry out tree planting [54], implying that the similarity in land size ownership indicates the potential of households without woodlots to establish woodlots. This raises the question, however, as to why households with similar land size do not engage into woodlot establishment irrespective of the high intension to establish woodlots.…”
Section: Differences In Household Endogenous and Demographic Traits Asupporting
confidence: 82%
See 1 more Smart Citation
“…The results concede with other findings in that households tend to minimize labor inputs, leading to low quantities and qualities of tree farm outputs [53]. As observed by similar studies from the tropics, farmers with more land resources are able to carry out tree planting [54], implying that the similarity in land size ownership indicates the potential of households without woodlots to establish woodlots. This raises the question, however, as to why households with similar land size do not engage into woodlot establishment irrespective of the high intension to establish woodlots.…”
Section: Differences In Household Endogenous and Demographic Traits Asupporting
confidence: 82%
“…Negative experiences from woodlot farmers in neighboring villages also play a part in this regard. This creates insecurity with regard to land ownership and product use, and hence the view that woodlot establishment is an unsecure venture by the households [54]. Moreover, knowledge on land use PLRs is not well disseminated by the extension agents hence households obtain partial and outdated information.…”
Section: Knowledge On Land Use Plrs Towards Woodlot Establishmentmentioning
confidence: 99%
“…Land availability, low income and lack of labour, which was in many cases linked to health problems and/or old age, were limiting factors for tree planting among the non-growers. Access to land, not the cash income, defines households' interest to plant trees, which is in line with the findings of Kulindwa (2016). Land use pressure induced by population growth and escalated by the likely impacts of climate change (United Republic of Tanzania 2015) will remain high in Tanzania for years to come and increasing pressure for more agricultural land is likely to push tree growing into more remote areas and poorer sites, where expected returns on tree growing are smaller due to longer rotation ages and/or lower stocking rates that may need to be applied (Capitani et al 2016;Call et al 2017).…”
Section: Future Of Smallholder Tree Growing In Tanzaniasupporting
confidence: 78%
“…In another study, Mekonnen and Damte (2011) found that educational levels of household heads significantly influence tree planting behaviour in Ethiopia. However, a study that was conducted by Kulindwa (2016) found that education was statistically insignificant in influencing tree planting.…”
Section: Discussionmentioning
confidence: 98%
“…It was found that security of land tenure rights, land areas owned, previous involvement in tree conservation, household size and cropland areas were the statistically significant factors. Kulindwa (2016) also analyzed the factors influencing tree planting behaviour in Tanzania using the Heckman selection bias modeling. It was found that tree planting was significantly influenced by households' land holdings, tree planting programme awareness, and farmers' age.…”
Section: Introductionmentioning
confidence: 99%